2010
DOI: 10.1007/s13206-010-4206-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of gene expression for pigmentation in Chinese cabbage (Brassica rapa)

Abstract: Anthocyanins are a major class of flavonoids that are produced in the tissues of many plant species in response to environmental signals. The pigmentation of Chinese cabbage (Brassica rapa) was analyzed using newly developed 300K Brassica rapa microarrays. The significantly expressed genes were analyzed by clusters of orthologous groups (COGs) and hypergeometric analyses for transcription factors associated with anthocyanin pigmentation. The candidate genes were classified into 11 groups that exhibited functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The polygenic effect agrees with Kim et al. () who conducted a microarray study on pigmentation of Chinese cabbage ( B. rapa ) where 38 unknown genes were identified that potentially play a role in anthocyanin biosynthesis. A blast analysis conducted with seedling anthocyanin DArT markers sequences had hit on both chromosome A7 of consensus map and B. rapa genome sequences.…”
Section: Discussionsupporting
confidence: 88%
“…The polygenic effect agrees with Kim et al. () who conducted a microarray study on pigmentation of Chinese cabbage ( B. rapa ) where 38 unknown genes were identified that potentially play a role in anthocyanin biosynthesis. A blast analysis conducted with seedling anthocyanin DArT markers sequences had hit on both chromosome A7 of consensus map and B. rapa genome sequences.…”
Section: Discussionsupporting
confidence: 88%
“…This microarray is a powerful tool for studying the complex biological responses involved in anthocyanin pigmentation biosynthesis in Chinese cabbage 43 . We performed a five-stage analysis to evaluate gene expression profiles during anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used 300K Brassica rapa (version 2.0) microarrays 43 . These microarrays were designed such that seven probes could cover a 150-bp region at the 3′ end of genes.…”
Section: Microarray Experimentsmentioning
confidence: 99%
“…Microarray can be used to elucidate relationships between genes and enables genome-wide analyses under numerous conditions 21 . Several studies have demonstrated the successful use of microarray to analyze gene expression changes in a number of crop species, including black rice 22,23 . Using Ds insertion lines is one of the most important methods in rice breeding and in understanding the function of the genome, including studying gene functions in plants with the Activator/Dissociation (Ac/Ds) transposon 24 .…”
Section: Original Researchmentioning
confidence: 99%